STUDI EKSPLORATIF DAMPAK COVID-19 TERHADAP KEGIATAN PEMBELAJARAN ONLINE MAHASISWA JURUSAN AKUNTANSI POLITEKNIK NEGERI AMBON - Albertus Lalaun (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2021)
The Covid-19 virus began to emerge at the end of 2019 in China and continued to endemic until the end of January 2020. In Indonesia, this virus has been infected, precisely in March until now, and has greatly impacted various areas of life. In the field of education, there is an online learning policy (online) from elementary school to university levels, this step is to stop the spread of COVID-19 in Indonesia. This research uses qualitative research with an exploratory study method. The informants consisted of 2 students and 2 lecturers who carried out online learning activities. Data collection using interviews. The results obtained were, the implementation of learning activities in the Accounting Department of the Ambon State Polytechnic when Covid-19 was felt to be less effective and efficient, several applications and online websites used by lecturers to conduct lectures were Web Classroom, Zoom Meeting, video conference, telephone or live chat. and Whatsapp Messenger, but some lecturers only use zoom and Whatsapp Messenger, the implementation of online learning activities using applications is still being carried out during this covid 19 pandemic. The results of online learning activities are still not optimal.